Slow magnetic relaxation in a homo dinuclear Dy(iii) complex in a pentagonal bipyramidal geometry. Issue 37 (15th September 2020) - Acharya, Joydev; Ahmed, Naushad; Flores Gonzalez, Jessica; Kumar, Pawan; Cador, Olivier; Singh, Saurabh Kumar; Pointillart, Fabrice; Chandrasekhar, Vadapalli
Abstract : A homodinuclear complex of Dy(iii ) has been synthesised and characterised. Magnetic analysis disclosed a field-induced slow magnetic relaxation of the complex. Abstract : We hereby report a dinuclear Dy(iii ) complex, [Dy(LH3 )Cl2 ]2 ·2Et2 O (1 ) (LH4 = 2, 3-dihydroxybenzylidene)-2-(hydroxyimino)propanehydrazide where both the metal centres are in a pentagonal bipyramidal (PBP) geometry with the axial positions being occupied by negatively charged Cl − ions. The complex as well as it's 10% diluted analogue (110 ) do not show zero-field SMM behaviour. However, in the presence of small optimum dc fields the slow relaxation of magnetization was displayed. The effective energy barrier for 110 at 800 Oe of applied field was extracted as 83(17) K with τ 0 = 2(4) × 10 −12 s. Through a combined experimental and ab initio electronic structure calculations studies we have thoroughly analysed the role of the ligand field around the Dy(iii ), present in pentagonal bipyramidal geometry, in contributing to the slow relaxation of magnetization.